Composition, antioxidant and antimicrobial activities of Eleutherococcus senticosus fruit extracts - Daehan Jang,Junwoo Lee,Seung Hee Eom,Seung Min Lee,Jinsu Gil,Heung Bin Lim,Tae Kyung Hyun (Journal of Applied Pharmaceutical Science, 2016)
This study was designed to examine the in vitro antioxidant and antimicrobial activities of essential oil and crude methanolic (MeOH) extract of Eleutherococcus senticosus (common name, Siberian ginseng) fruit and its partitioned fractions, including hexane, ethyl acetate (EtOAc), n-butanol (BuOH) and aqueous. 1,1-dephenyl-2-picryl-hydrazyl free radical scavenging and reducing power assay suggest that antioxidant activity of EtOAc and BuOH fractions is due to the reducing ability of the antioxidant against oxidative effects of reactive oxygen species. In addition, the essential oil of Siberian ginseng fruit showed remarkable antimicrobial activity against Kocuria rhizophila (MIC = 125 µg/ml), Micrococcus luteus (MIC = 500 µg/ml), and Escherichia coli (MIC = 63 µg/ml). The chemical compositions of the essential oil obtained by the simultaneous steam-distillation and extraction method were analyzed using GC-MS; trans-caryophyllene (21.7%), humulene (7.4%), bicyclogermacrene (6.0%), (+) spathulenol (4.5%), germacrene-D (3.2%), tau-muurolol (2.5%) and delta-cadinene (2.3%) were found as main constituents. Furthermore, HPLC analysis identified ursolic acid as one of the principal components in Siberian ginseng fruit extract. Although this study has been carried out by in vitro assay, these results suggest that Siberian ginseng fruit may be a good candidate as a source of antioxidant and antimicrobial ingredients.
Keywords: Eleutherococcus senticosus,Essential oil,Antioxidant,Antimicrobial,Ursolic acid.